EVALUASI KINERJA GAYA GEMPA PADA GEDUNG BERTINGKAT DENGAN ANALISIS RESPON SPEKTRUM BERDASARKAN BASE SHARE, DISPALACEMENT, DAN DRIFT MENGGUNAKAN SOFTWARE ETABS ( STUDI KASUS : HOTEL DI DAERAH KARANGANYAR) - Donny Baiquny Febbrian; Agus Setiya Budi; Kusno Adi Sambowo (Matriks Teknik Sipil, 2014)
Indonesia as an archipelago State and State which are included in the ring of fire because the path of it was onmeet the Australian plate, the Eurasian plate and the Pacific plate. Have a high enough percentage shift resultingin Indonesian territory vulnerable to earthquake shaking.This study aims to determine the performance evaluationmeasures earthquake forces in buildings by using the response spectrum dynamic analysis based on sharebase, displacement and drift in the Immediate Occupancy level category.Analysis of dynamic response spectrumin the X direction and in the Y direction generate Vdinamik greater than 0.85 Vstatik, so the final value of thedynamic response of building structures against earthquake loading due to the influence of the earthquake nominalplan meets the requirements of SNI 03-1726-2012. Based on the value of displacement in the X direction andthe Y direction, the drift rate due to the effect of earthquakes smaller plan than [(0.03/R)H] so it can be safelyconcluded the serviceability limit the performance evaluation requirements in accordance with SNI 03-1726-2002, and the maximum drift level of the building structure due to the influence of earthquakes in the condition ofthe building plans on the verge of collapse less than [0.02H] so it can be safely concluded the ultimate limits ofperformance evaluation requirements in accordance with SNI 03-1726-2002. The maximum total drift and inelasticdrift in the X direction and the Y direction, so that when it is viewed according to ATC - 40, it is includedin the level immediate occupancy category.